A Muted Fury: Populists, Progressives, and Labor Unions Confront the Courts, 1890-1937 - William G. Ross (Princeton University Press, 2014)
THE PROPER SCOPE of judicial power in America is a source of perennial controversy. During every period of the Republic's history, critics of the courts have assailed the judiciary with invective and have proposed measures to curtail the institutional prerogatives of the courts.1 Many periods of acute conflict have received careful scholarly attention. Indeed, the Jeffersonian antagonism toward the Marshall Court, the firestorm over the Dred Scott decision, the controversies of the Reconstruction era, Franklin Roosevelt's Courtpacking plan, and the bitter reactions to the Warren Court's activism have become staples of the lore of American legal history. One period of fierce controversy, however, has received less attention than it deserves. Between 1890 and 1937, populists, progressives, and labor leaders subjected both state and federal courts to vigorous and persistent criticism and proposed numerous plans to abridge judicial power. The conflict between Franklin D. Roosevelt and the Supreme Court that reached its denouement in 1937 was merely the culmination of a struggle that had raged with varying degrees of intensity for a half century. Decades before the New Dealers denounced the Supreme Court's "nine old men," Chief Justice Walter Clark of North Carolina, the tireless scourge of the federal judiciary, had railed against the "five elderly lawyers" who composed the Supreme Court's conservative majority. 2 Clark and countless other antagonists of the courts between 1890 and 1937 alleged that a "judicial oligarchy" had usurped the powers of Congress and thwarted the will of the people by interfering with the activities of labor unions and nullifying legislation that was designed to ameliorate the more baneful effects of the Industrial Revolution. This book traces and analyzes the grievances of these critics of the judiciary and their myriad proposals for judicial reform. Prolific and often shrill in their denunciations of the judiciary and their demands for curtailment of judicial power, the antagonists of the courts were anything but mute. It is the thesis of this book, however, that the intense fury of populists, progressives, and labor unions was nonetheless muted by many factors and circumstances that were both internal and external to their reform movements.